Pemahaman Guru PAI tentang Hakikat Manusia dan Daya-daya Ruhani dalam Pembelajaran: Studi Fenomenologis pada SDIT Mutiara Hati - Rahmi, Laila Kamilatu; Putra, Heru Yama; Fadriati, Fadriati; Suryana, Ermis (Lembaga Yasin AlSys, 2025)
Although the nature of the human being and spiritual faculties has been widely discussed in the Islamic education literature, research that specifically explores how guru PAI interpret and implement these concepts in classroom practice through a phenomenological approach remains very limited. This gap highlights the need for studies that examine teachers’ authentic experiences in understanding fitrah, akal, and qalb as pedagogical foundations, particularly in the context of Sekolah Dasar Islam Terpadu. This study aims to describe guru PAI’s understanding of human nature, identify their interpretations of students’ spiritual faculties, and explain how these understandings influence pedagogical strategies at SDIT Mutiara Hati. The research employs a qualitative approach with an interpretative phenomenological design, involving six teachers selected through purposive sampling. Data were obtained through in-depth interviews, classroom observations, and documentation, and were analyzed using phenomenological stages that include horizontalization, clustering of essential themes, and interpretation of meaning. The findings show that all teachers view humans as beings endowed with fitrah, akal, and qalb, which are manifested in classroom practice through habituation of moral conduct, role modeling, reflective dialogue, and the facilitation of emotional–spiritual experiences. Students’ rational faculties are activated through value-based discussions and reflective questioning, the qalb is nurtured through gentle approaches and the presentation of exemplary stories, and fitrah is preserved through daily spiritual activities and the habituation of positive behaviors. These findings contribute theoretically to the development of a holistic Islamic education paradigm that integrates cognitive, affective, and spiritual dimensions. Practically, the study underscores the importance of strengthening teachers’ competence in spiritual guidance and the need for school support in building a learning culture oriented toward character and spiritual formation, while also opening avenues for further research on the development of instruments for assessing spiritual dimensions and more systematic learning models grounded in fitrah, akal, and qalb.